Kajian Tingkat Keterjangkauan Dan Pola Preferensi Bermukim Masyarakat Berpenghasilan Rendah Dalam Mengakses Rumah Di Kecamatan Ngaliyan - Naufal Rabbani Priyandianto; Asnawi Manaf (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Housing development built by government and private developers are currently not able to provide affordable housing and according to the preferences of the low-income community. This condition causes a lot of low-income people prefer to inhabit the house who doesn’t belong to them (rent) and be resident commuters, so they were not able to afford their own house, due to limited purchasing power. This research aims to determine the level of affordability and preference patterns of low-income communities in the Kecamatan Ngaliyan. The research used Descriptive Quantitative Method. This research shows that the majority of low-income communities in the Kecamatan Ngaliyan who work as industrial and informal workers, are still not able to access the house according to 64% of the total respondents. While there are only 36% of respondents who work as private and civil employees have been able to reach the house. Respondents have the ability to make mortgage about Rp 300,000, - - Rp 400.000, -. While the lowest price of minimal house mortgage is Rp 650,000, - - Rp 750.000, -. This conditions indicate that there’s no suitable house  for the financial condition of the community. There are 4 factors that affect the preferences of low-income people living in the Kecamatan Ngaliyan, such as Physical and Building Location Factor, Infrastructures Factor, Social Environmental Factor, and Perception and Economic Conditions Factor. The pattern of community preference also strongly affected by the type of job, income level, and lifestyle.